Influence of Work-Life Balance on Mental Health Among Nurses: The Mediating Role of Psychological Capital and Job Satisfaction - Zhang J; Rehman S; Addas A; Ahmad J (Psychology Research and Behavior Management)
Jian Zhang,1 Shazia Rehman,2 Abdullah Addas,3,4 Jamal Ahmad5 1Mental Health Education Center, Nanyang Vocational College of Agriculture, Nanyang, Henan, 473000, People’s Republic of China; 2Department of Psychiatry, National Clinical Research Center for Mental Disorders, and National Center for Mental Disorders, the Second Xiangya Hospital of Central South University, Changsha, Hunan, 410011, People’s Republic of China; 3Department of Civil Engineering, College of Engineering, Prince Sattam Bin Abdulaziz University, Al-Kharj, 11942, Saudi Arabia; 4Landscape Architecture Department, Faculty of Architecture and Planning, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 5Health Department, Nishtar Medical College & Hospital Multan, Multan, 59070, PakistanCorrespondence: Shazia Rehman, Department of Psychiatry, National Clinical Research Center for Mental Disorders, and National Center for Mental Disorders, the Second Xiangya Hospital of Central South University, Changsha, Hunan, 410011, People’s Republic of China, Tel +86-13308429613, Email rehmanshazia.malik@gmail.comBackground: Nurses constitute the backbone of the healthcare sector, often confronting elevated levels of work-related stress and emotional demands that can profoundly impact their mental well-being. Mental health is critical to nursing practice as it directly influences job performance, patient care quality, and workforce sustainability. This study examines the effects of work-life balance on the mental health of nurses in Pakistan while examining the intermediary effects of psychological capital and job satisfaction.Methods: A descriptive cross-sectional survey was conducted from twenty-seven public and private hospitals in Multan, Pakistan, between December 2023 and March 2024. The research employed meticulously validated measurement tools: Work-Life Balance (WLB) Scale, Psychological Capital Questionnaire 12 (PCQ-12), Job Satisfaction Survey (JSS), and General Health Questionnaire 12 (GHQ-12) to collect data on 578 participants. Statistical analysis was performed using SPSS and AMOS to investigate direct and indirect relationships among study constructs.Results: The results indicated that work-life balance positively influences both psychological capital (β = 0.083, p < 0.05) and job satisfaction (β = 0.113, p < 0.01), which, in turn, significantly contributes to better mental health outcomes among nurses. Sequential mediation analysis confirmed that psychological capital and job satisfaction (Indirect effect=0.022, 95% CI: 0.01– 0.037) mediate between work-life balance and mental health, suggesting that a healthy work-life balance enhances psychological resources and job satisfaction, thereby improving mental health.Conclusion: The findings highlight the importance of fostering a supportive work environment within the nursing community that promotes work-life balance, enhances psychological resources, and improves job satisfaction to maintain nurses’ overall mental health.Keywords: Work-Life Balance, Mental Health, Psychological capital, Job Satisfaction, Nurses